ChemInform Abstract: A One‐Pot Process for Palladium Catalyzed Direct C—H Acylation of Anilines in Water Using a Removable ortho Directing Group. Issue 40 (30th September 2014) - Szabo, Fruzsina; Simko, Daniel; Novak, Zoltan
Abstract Comparison of the three step one‐pot process with the reaction sequence with full isolation of the reaction intermediates discloses comparable overall yields.